2021
DOI: 10.3389/fpubh.2021.690645
|View full text |Cite
|
Sign up to set email alerts
|

Multi-State Analysis of the Impact of Childhood Starvation on the Healthy Life Expectancy of the Elderly in China

Abstract: Background: Child malnutrition is not only common in developing countries but also an important issue faced by developed countries. This study aimed to explore the influence and degree of childhood starvation on the health of the elderly, which provides a reference for formulating health-related policies under the concept of full lifecycle health.Methods: Based on the Chinese Longitudinal Healthy Longevity Survey (CLHLS) in 2008, 2011, and 2014, this study took a total of 13,185 elderly people aged 65–99 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Previous studies interviewed 13,185 individuals aged 65–99 years and found that childhood experiences of hunger affect socioeconomic status in adult life, which, in turn, can affect health outcomes in older adults ( 31 ). Our findings showed that high educational level and financial independence may reduce the probability of childhood hunger-mediated frailty in older age.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies interviewed 13,185 individuals aged 65–99 years and found that childhood experiences of hunger affect socioeconomic status in adult life, which, in turn, can affect health outcomes in older adults ( 31 ). Our findings showed that high educational level and financial independence may reduce the probability of childhood hunger-mediated frailty in older age.…”
Section: Discussionmentioning
confidence: 99%
“…However, in studies about older Chinese people, the importance of health care services in the process of health level changes throughout the life cycle of individuals is not explored. Also, the indicators used to measure health level are mostly single measures of physical or psychological aspects of old age, which do not comprehensively reflect the quality of life of the older population (13)(14)(15)(16). Additionally, cross-sectional data does not reflect the overall development trend of the health of the older population, so it is insufficient to have an overall understanding of the mortality and health level of the older population in China.…”
Section: Introductionmentioning
confidence: 99%